Math for all (Memorias Sifored - Encuentros Educación UAN, 2021)
It is exposed how to use games as an innovative tool within the District Educational Institution (IED) Colegio Paulo Freire to contribute to the inclusive development of mathematical logical thinking and attitude towards discipline.
Keywords: game; motivation; play-based learning